Data Documentation v1.0: Remote sensing quantifies widespread abundance of permafrost region disturbances across the Arctic and Subarctic. - Nitze, Ingmar; Grosse, Guido; Jones, Benjamin M; Romanovsky, Vladimir E; Boike, Julia (PANGAEA, 2018)
Here we quantify the abundance and distribution of three primary permafrost region disturbances (PRD; lakes and their dynamics, wildfires, retrogressive thaw slumps) using trend analysis of 30-m resolution Landsat imagery from 1999-2014 and auxiliary datasets. The dataset spans four continental-scale transects in North America (Alaska, Eastern Canada) and Eurasia (Western Siberia, Eastern Siberia), covering 2.3M km² or ~10% of the permafrost region. This data publication contains geospatial vector files (polygons) of the perimeters of PRD. The data are subdivided by PRD type (lakes, wildfire, retrogressive thaw slumps) and further subdivided by study region (T1_WS, T2_ES, T3_AK, T4_EC). T1_WS: Western SIberia T2_ES: Eastern Siberia T3_AK: Alaska T4_EC: Eastern Canada The datasets are documented in detail in the linked document (Nitze_etal_2018: Data Documentation v1.0).
Remote sensing quantifies widespread abundance of permafrost region disturbances across the Arctic and Subarctic, Datasets
Keywords: AWI_PerDyn; DUE-GlobPermafrost; ESA Data User Element - GlobPermafrost; Permafrost Research (Periglacial Dynamics) @ AWI; PETA-CARB; Rapid Permafrost Thaw in a Warming Arctic and Impacts on the Soil Organic Carbon Pool